Propaganda in the Context of “Parable – Paradigm” - Khazagerov, Georgij (Respectus Philologicus, 2019)
This article presents two strategies of manipulation: metaphoric and metonymic. Metaphoric type is a foundation of the totalitarian propaganda. The optimal environment for this type of propaganda is a new urban population, the former peasants. Its best information distribution channel is a newspaper. Its Achilles’ heel is the involvement of population masses in creating and developing of metaphors, which makes perception of metaphors less “automatic” and more thought-provoking. Metonymic type of propaganda is based on categorization of reality through the understanding of what is typical. Such propaganda does not create a holistic worldview and is suitable for an authoritarian rather than classical totalitarian government. Its optimal environment is people who have experience in virtual reality. The ideal information channel is TV. The recipient of this propaganda is not involved in its co-creation, which makes the system more resistant to self-analysis. Nevertheless, like in case of any hidden linguistic manipulation, the intensive use of metonymic type of propaganda reduces its manipulative potential.